MICROSPONGES: AN INNOVATIVE STRATEGY FOR DRUG DELIVERY SYSTEM (International Journal of Food and Nutritional Sciences, 2022)
Conventional topical formulations are intended to work on the surface of the skin. Normally, upon application such formulations release their active ingredients and producing a highly concentrated layer of active ingredient that is quickly absorbed. Therefore, need exists for a system to increase the amount of time that an active ingredient is present either on skin surface as well as within the epidermis, at the same time, minimizing its transdermal penetration in the body. Recently, microsponge delivery system (MDS) has been successively addressed for the controlled release of drugs onto the epidermis with assurance that the drug remains chiefly localized and does not enter the systemic circulation in major amounts. MDS is a unique technology for the controlled release of topical agents, also use for oral as well as biopharmaceuticals (peptides, proteins and DNA-based therapeutics) drug delivery. It consists of microporous beads having a range of 10-25 microns in diameter that possess a versatility to entrap wide range of active agents. This review article covers methods of preparation, release mechanism, characterization and applications of microsponge delivery system with patent information and marketed formulations.